2004
DOI: 10.1002/app.20808
|View full text |Cite
|
Sign up to set email alerts
|

Melt reaction in blends of poly(3‐hydroxybutyrate) (PHB) and epoxidized natural rubber (ENR‐50)

Abstract: Melt reaction in blends comprising immiscible biopolymer, poly(3-hydroxybutyrate) (PHB), and epoxidized natural rubber with 50 mol percent level of epoxidation (ENR-50), prepared by solvent-casting, has been studied. Differential scanning calorimetry (DSC) technique was used to measure the heat of reaction under isothermal annealing. The heat of reaction increases with respect to PHB and ENR-50 content as long as they constitute the dispersed phases and exhibits a maximum at about 50% PHB. A reaction mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 8 publications
(13 reference statements)
2
49
0
3
Order By: Relevance
“…The carboxylic terminal groups of the degraded PHB react with other compatible functionalized polymers at sufficiently high temperatures. In fact, our group has previously reported upon melt reactions in blends of PHB and a modified natural rubber, namely 50% epoxidized natural rubber, ENR-50 [17]. In this case, oxirane ring opening reactions were induced by carboxylic terminal groups of the degraded PHB upon heating the PHB/ENR-50 blend to slightly above the melting temperature of PHB.…”
Section: Introductionmentioning
confidence: 86%
“…The carboxylic terminal groups of the degraded PHB react with other compatible functionalized polymers at sufficiently high temperatures. In fact, our group has previously reported upon melt reactions in blends of PHB and a modified natural rubber, namely 50% epoxidized natural rubber, ENR-50 [17]. In this case, oxirane ring opening reactions were induced by carboxylic terminal groups of the degraded PHB upon heating the PHB/ENR-50 blend to slightly above the melting temperature of PHB.…”
Section: Introductionmentioning
confidence: 86%
“…Therefore, there has been a great deal of interest in studying the thermal degradation behavior of PHB and other related poly(hydroxyalkanoate)s [29][30][31][32][33][34][35] . Also studies seeking to improve the thermal stability of PHB by grafting chemicals in PHB chain [33,36] , and adding polymeric additives in PHB matrix [37,38] have been developed. The thermal degradation behavior of PHB has been discussed in many works [14,20,21,30,[39][40][41][42] , in which a random chain scission reaction (β-elimination) involving a six-membered ring transition state ( Figure 1) has been considered as the main mechanism based on typical structures of pyrolysis products, i.e., crotonic acid and oligomers with a crotonate end group, i. e., unsaturated end groups.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that most of the polymer blends are immiscible and tend to separate into macroscopic phases and reveal clear individual glass transition temperatures [3,8,9,19]. Lee et al [20] reported that in blends of PHB/ENR-50, the carboxyl end group of degraded PHB and the epoxide group of ENR are reactive and may affect chemical and physical, as well as structural changes at the interfaces of the immiscible PHB and ENR phases. They also pointed out that the extent of miscibility is more pronounced in molten state.…”
Section: Introductionmentioning
confidence: 99%